Dėl kankorėžių pavadinimų kilmės - Ambrazas, Saulius (Baltistica, 2010)
On the origin of cone termsAlgirdas Sabaliauskas (1972) on the basis of the rough copy of the maps of the Atlas of the Lithuanian language (cf. Lietuvių kalbos atlasas 1, Map 93) established, that čiū̃tė ‘cone’ (used in the Western part of North Low Lithuanian dialect not far from the area where kiaũlė, kiaulẽlė, kiaulìkė have the meaning of cone) is formed not from čečka, čyčka, the varriants of Slavic borrowing šyškà (characteristic of some West High Lithuanian dialects), as Ernst Fraenkel (1955–1965, 72, 77) thought, but from onomatopoeic names of pig, cf. Lith. čiúotė, čiúotis; čiūkà, čiū̃kas, Latv. čūčis.During preparation of Atlas of the Baltic Languages the revision has been made of other cone terms in Lithuanian dialects. The greatest part of them is also formed from onomatopoeic words, cf.  kukùtis (: kùkti ‘give a scream, utter’, kaũkti ‘howl, wail, hoot’), gurgùtis (: gur̃gti ‘rumble, grumble’), burkùtis (: bur̃kti ‘purr, mutter; gramble’, burkúoti ‘coo, purr’), baubùkas (: baũbti ‘moo, bellow, roar’), bū̃kas, bùkas (: baũkti ‘moo, bellow, roar; bleat, baa; shout, shriek’, bū̃kti ‘bleat, baa, moo’) a. o.In the similar way the origin of the older cone terms has been explained: Lith. kìrkužė, Latv. cirkuzis ‘cone’  (cf. Lith. kir̃kti ‘cluck; weep; croak; squeak, creak’, Latv. cir̃kstêt ‘chirp, chirr; squeak, creak’), Lith. kankórėžis ‘cone’ (cf. kañkalas ‘clapper’ and rė́žti ‘cut, curve’), Lith. skujà ‘needle; cone’, Latv. skuja ‘needle’ (cf. Lith. skuĩstas ‘bush; pine forest’, skuĩstis ‘thick-set fir-grove’; kuĩstas ‘bush’, kuĩtas, kuĩtis ‘thick-set coniferous forest’; skuĩsti ‘play pranks, be naughty, romp, rage, rave’, kuĩsti ‘rummage, ransack; dig up the ground; rush’, Latv. skuit, skuju ‘shave, scrape, peel; cut, clip; clean’).
Keywords: lietuvių kalba; kankorėžių pavadinimai; leksika